Analysis of Electrical Energy & Water Consumption in a Hostel Building through Regression Analysis - ., Siddhartha; Yeswanth Pai, Maya (International Journal of Engineering and Technology, 2018)
This paper focuses on determination of building factorsÂ Â affectingÂ Â electricityÂ Â andÂ Â waterÂ Â consumptionÂ Â ofÂ Â a residential building in India. Among various factors like temperature, occupancy schedules, building envelope, lighting and HVAC Loads, two determinant factors are selected after collecting annual energy and water consumption information for the residential building for a period of one year. Along with that, weather information for the same building is collected and a correlation analysis is performed to determine the effect of the determinant factors on the consumption. Based on the correlation results, the factor affecting the consumption is determined. After which using a statistical method i.e. Linear Regression Analysis, the best possible model is determined based on the results obtained from the regression. The model capable of predicting the consumption with least error and high value of correlation is chosen and the equation of the model is used for prediction purposes. Â Â